Bürgerschaftliches Engagement in Ostdeutschland : Potenziale und Perspektiven - Backhaus-Maul, Holger 1960- Hrsg; Ebert, Olaf; Jakob, Gisela; Olk, Thomas 1951-2016 (Leske + Budrich, 2003)
Potenziale und Perspektiven